Case Report: Two Chinese Infants of Sengers Syndrome Caused by Mutations in AGK Gene - Wang, Benzhen; Du, Zhanhui; Shan, Guangsong; Yan, Chuanzhu; Zhang, Victor Wei; Li, Zipu (Frontiers in Pediatrics, 2021)
Sengers syndrome (OMIM #212350) is a rare autosomal recessive disorder due to mutations in Acylglycerol kinase (AGK) gene. We report two cases that were diagnosed clinically and confirmed genetically. Both infants had typical clinical features characterized by hypertrophic cardiomyopathy, bilateral cataracts, myopathy, and lactic acidosis, and heart failure was the most severe manifestation. Genetic testing of a boy revealed a homozygous pathogenic variant for Sengers syndrome in AGK (c.1131+2T>C) which was classified as likely pathogenic according to the ACMG guideline, besides, his skeletal muscle biopsy and transmission electron microscope presented obvious abnormity. One girl had compound heterozygous (c.409C>T and c.390G>A) variants of AGK gene was identified in the proband and further Sanger sequencing indicated that the parents carried a single heterozygous mutation each. After the administration of “cocktail” therapy including coenzyme Q10, carnitine, and vitamin B complex, as well as ACEI, heart failure and myopathy of the boy were significantly improved and the condition was stable after 1-year follow-up, while the cardiomyopathy of the girl is not progressive but the plasma lactate acid increased significantly. Conclusion: We present the first report of two infants with Sengers syndrome diagnosed via exome sequencing in China.